WOMEN IN REPRODUCTIVE SCIENCE: Reproduction down under. Issue 6 (December 2019) - Renfree, Marilyn B
Abstract : Australia is home to a unique assembly of mammals – the marsupials and monotremes. Despite this uniqueness, they have been largely ignored by the biomedical scientific community, and yet study of marsupials has contributed to modern research on reproduction, development, evolution, conservation, molecular and comparative genomics. My lifetime passion for these long-neglected Australian fauna has led to unexpected discoveries and insights that challenged assumptions and opened up new areas of international research. I used a range of disciplinary expertise to pursue the study of these unique mammals. My main experimental species has been the tammar wallaby that I have used as a model species to investigate and understand not only biomedical problems but also to provide knowledge that is critical for the continued conservation and management of Australia's dwindling native mammals. This model provided more than a few surprises for me and my wonderful team of students, post-docs and collaborators about how hormones, genes and signalling molecules control reproductive biology and development in a wider context as well as how the interactions of the environment with mother and conceptus, with mother and fetus and mother and young ultimately control most aspects of successful reproduction in mammals.